Automated data analysis for consecutive images from droplet combustion experiments - Dembia, Christopher L (Image analysis and stereology, 2012)
A simple automated image analysis algorithm has been developed that processes consecutive images from high speed, high resolution digital images of burning fuel droplets. The droplets burn under conditions that promote spherical symmetry. The algorithm performs the tasks of edge detection of the droplets boundary using a grayscale intensity threshold, and shape fitting either a circle or ellipse to the droplets boundary. The results are compared to manual measurements of droplet diameters done with commercial software. Results show that it is possible to automate data analysis for consecutive droplet burning images even in the presence of a significant amount of noise from soot formation. An adaptive grayscale intensity threshold provides the ability to extract droplet diameters for the wide range of noise encountered. In instances where soot blocks portions of the droplet, the algorithm manages to provide accurate measurements if a circle fit is used instead of an ellipse fit, as an ellipse can be too accommodating to the disturbance.
Keywords: automated data analysis; avtomatska analiza podatkov; image analysis; slikovna analiza; zgorevanje; combustion